A Long Distance Underwater Visible Light Communication System With Single Photon Avalanche Diode - Chao Wang; Hong-Yi Yu; Yi-Jun Zhu (IEEE Photonics Journal)
Underwater visible light communication (UVLC) is of great interest to the military, industry, and the scientific community. In this paper, a long-distance UVLC system is designed, where the half power angle of light-emitting diode (LED) is narrowed to enhance the optical intensity at the transmitter, and a single photon avalanche diode (SPAD) is employed at the receiver to improve the detection sensitivity. A two-term exponential channel model of a long distance UVLC system with a SPAD receiver is established, and the channel parameters are obtained by Monte Carlo numerical simulation. Furthermore, the SPAD detection algorithm and the optimal detection threshold of the UVLC system are proposed. Simulation results show that the communication distance could be extended to 500 m in pure seawater.